A "patchwork" for peace: institutions and activities in Kenya's northern drylands. Issue 3 (4th March 2018) - Bond, Jennifer; Mkutu, Kennedy
ABSTRACT: Despite the plethora of peacebuilding and conflict management institutions operating in Kenya, peace is often elusive in the northern drylands. With a lack of strong conflict management and peacebuilding processes in place from government, despite an active framework for such processes, non-state actors have filled this conflict management space. In this article, we draw on the institutional bricolage and sustainable peace literatures to understand peacebuilding through the frame of legitimacy. Using Laikipia County, Kenya as a case study, we draw on empirical findings which show that different institutions are attributed legitimacy differently. We find that while the Laikipia Professional Peace Caravan was seen as legitimate to pastoralists in conflict areas, its legitimacy was challenged by other practitioners. Similarly, while pastoralists viewed homeguards as legitimate, practitioners did not. The analysis links to discussions of the "business of peace" within the literature to consider why long-term peace has been elusive in Kenya's northern drylands.